1997
DOI: 10.1079/nrr19970007
|View full text |Cite
|
Sign up to set email alerts
|

Diet and haemostatic processes

Abstract: Diet plays an important role in the primary and secondary prevention of cardiovascular disease. The growing perception that abnormal haemostatic processes of coagulation, platelet aggregation and fibrinolysis contribute to cardiovascular disease aetiology motivated this review on the relationships of diet, specific foods and nutrients with haemostatic function. Functional endpoints that reflect the function and status of some of these processes and which can be measured in dietary trials are identified. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…Several dietary intervention studies have shown that FVII is influenced by the diet [64][65][66][67], and total dietary fat intake appears to be the main determinant of postprandial FVII coagulant activity (FVIIc) [68]. One effect of olive oil, a fundamental component of MeD, is on FVII, a key protein in thrombosis and an important risk factor for ischemic heart disease [69][70][71][72][73].…”
Section: Monounsaturated Fatty Acids and Factor Vii: Anti-thrombotic mentioning
confidence: 99%
“…Several dietary intervention studies have shown that FVII is influenced by the diet [64][65][66][67], and total dietary fat intake appears to be the main determinant of postprandial FVII coagulant activity (FVIIc) [68]. One effect of olive oil, a fundamental component of MeD, is on FVII, a key protein in thrombosis and an important risk factor for ischemic heart disease [69][70][71][72][73].…”
Section: Monounsaturated Fatty Acids and Factor Vii: Anti-thrombotic mentioning
confidence: 99%
“…n -3 PUFA is famous for its protective and modifying effects on a variety of diseases such as multiple sclerosis, major depression, atherosclerosis, ventricular arrhythmia and inflammatory or autoimmune diseases ( Nuernberg et al, 2005a ; Balk et al, 2006 ), and CLAs have been reported to be beneficial to human health because of their health-promoting properties such as the inhibition of carcinogenesis, a reduced rate of fat deposition, stimulation of the immune system, and reduced serum lipids in animal models ( Banni et al, 2002 ; Wu, 2004 ). However, an excessive consumption of SFAs such as C12:0, C14:0 and C16:0 may cause an atherogenic potential in humans ( Vorster et al, 1997 ) and may contribute to high coronary heart disease (CHD) mortality rates ( Williams, 2000 ; Rioux and Legrand, 2007 ). Additionally, a high proportion of n -6 PUFA can be deleterious for human health ( de Deckere et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review showed that prudent low fat, high fibre diet with the maintenance of ideal body weight might temper haemostatic risk factor for cardiovascular disorders [13]. In recent studies on African vegetarians, we found decreased BP, fibrinogen level and plasma viscosity [14,15], which we concluded may reduce predisposition of African vegetarians to major complications of CVD/IHD.…”
Section: Introductionmentioning
confidence: 47%